Sequential Migration, and the German Reunification - Angela Birk (Hamburg Institute of International Economics (HWWA), 2004)
The paper develops a sequential migration model and derives a worker's optimal policies for migration and employment. With the worker's simulated reservation wage functions for employment and migration, a stationary equilibrium is defined. In that equilibrium, stationary distributions of employed and unemployed stayers and movers over different states are derived. The analysis of Markov equilibria shows that mainly unemployed skilled and unskilled migrants will migrate. I have referred to this unemployed self-selection of skilled and unskilled migrants. Furthermore, in the stationary equilibrium, a trade off between equity and efficiency is derived and represents the adverse effects when a government fosters income increases too much.
Keywords: J61; E27; C61; 330; Sequential Migration; Markov Equilibria; German Reunification; Migrationstheorie; Regionale Arbeitsmobilität; Anspruchslohn; Markovscher Prozess; Deutschland